Lily Robert-Foley, The Duty to Presence - Helena Wahlström Henriksson (European Journal of Life Writing, 2024)
This book is an extended and formally mixed prose poem on the experience of becoming a mother, and particularly on spending the everyday every day with a baby, observing their development and attempting to record what one perceives. The author, Lily Robert-Foley is an American writer; she is also a translator, university teacher, and artist, and she is a playful thinker with an interest in feminist and queer resistance. Her previous publications range from a novel to a book on experimental translation; this is her first published book of poetry.